BEST PRACTICES OF SCIENCE TEACHING AMONG KINDERGARTEN SCHOOLS - M. Balmaña, Maria Cecilia; A. Ligsanan , Lucky Sonny (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This study documents the best practices in teaching science in kindergarten schools to create a model of teaching-learning process that develops scientific explanations from the students. Through a case study research design, the experiences of two kindergarten teachers were analyzed using the lenses of Pedagogical Content Knowledge and Elements of Scientific Explanation. Kindergarten teachers’ knowledge of orientation highlights the use of curriculum guides and the application of content knowledge and pedagogy learned from bachelor’s degree and master’s degree. Further analysis of class observations and students output led to the emergence of five thematic strands: 1) Teachers’ questions provide leading clues and are mostly answered in chorus by the students; 2) Students are active during activities and open questions but become passive receivers of information during explanation phase of the lesson; 3) The flow of inquiry-based instruction fulfils only students “claim” and “evidence” and was seldom extended to “reasoning” level; 4) Guidance of teachers through constant questioning helps students as a group provide scientific explanation that can reach reasoning level and; 5) The students are encouraged to share the result of their work in class.